Filantropía católica y sociedad civil: los voluntarios mexicanos de San Vicente de Paúl, 1845-1910 - Arrom, Silvia Mariana (Sociedad y Economía, 2006)
The lay conferences of Saint Vincent of Paul flourish in Mexico during the second half of the XIX Century within a wider movement of Catholic renovation. The two organizations, one of men and other of women, worked in poor relief and at the same time strengthened their faith. Voluntary workers contributed significantly to the development of the Mexican systems of education, public health and social relief. The number and national coverage of these groups show a strong tradition of philanthropy and voluntarism among the middle and high classes. In particular, the extraordinary success of Señoras de la Caridad demonstrates the femininization of charities in the period, which contributed to the expansion of the traditional boundaries of feminine orbit in Mexico.